Caracterização do gênero Scleroderma (Basidiomycotina) associado a povoamentos florestais exóticos no bioma Pampa, Brasil - Montagner, Daiane Fiuza (2014)
The genus Scleroderma Pers.: Fr. belongs to Order Boletales, Phylum Basidiomycota, and involves a group of fungi whose spore production occurs in an enclosed hymenium with passive basidiospores release. The main morphological characteristic of this genus are the size and ornamentation of the spores and mycorrhizal association with various tree species. The aim of this study is to identify Scleroderma species of Pampa biome region by using techniques of morphological analysis and molecular biology following specific methodologies. For an accurate analysis of the basidiospore ornamentation, scanning electron microscopy (SEM) was used. The specimens collected were deposited in the Herbarium SMDB of the Department of Biology, Federal University of Santa Maria - UFSM. For the analysis of phylogenetic relationships of selected species of Scleroderma was sequenced the rDNA (ITS1-5.8S-ITS2) region of some specimens collected or obtained from other herbaria for comparison with sequences deposited in GenBank. Two species were identified: S. albidum; S. citrinum and a specimen to genus level (Scleroderma sp.). We have generate 20 new ITS sequences, clustering most of them, in S. albidum clade, contrasting, however, with basidiome morphological variation initially observed; they represent the first records of this species for the ITS region in GenBank database. Sequences in clade S. albidum showed high similarity with some other nominated as S. bovista, S. aurantium and Sceroderma sp. from GenBank so, the latter sequences are considered as conspecific in the clade. S. citrinum clustered together with homonymous sequences from China, United States and Germany being conspedifics, and its basidiomes were the most identifable in study area by their morphological characteristics. The specimen ICN:154625, from Rio Grande do Sul, State nominated as S. verrucosum, showed high similarity with sequences of S. areolatum and were identified under the latter name. The phylogenetic analysis confirms the literature trend on formation of two major infrageneric clades combining, respectively, echinulate spores plus simple-septate hyphae and reticulate spores plus fibulae. Scleroderma sp. appeared phylogenetically isolated from these two main clusters suggesting a probable formation of a new clade combining echinulate spores and fibulae.